EFEK MEDIA SOSIAL DALAM MEMENGARUHI NIAT UNTUK BERDONOR DARAH - Monica Kristianti; Didik Setyawan; Sugiyarmasto . (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
his study aims to examine the effect of media influence on the influence of individual intention to donate blood donors. Data were obtained through questionnaires that have been distributed to social media users who have no experience of donating blood. The sampling technique used was pur posive sampling with a sample of 200. Hypothesis testing was carried out using SEM (Structural Equation Model) analysis. The results in this study indicate that three hypotheses are supported and one hypothes is is not. It can be inter preted that the donor's attitude is able to provide strength in increasing the user's intention to donate blood through the effects of social media and the interactivity of social media which can communicate in two ways not because of the features of social media.